Investigation of Hypolipidemic Activity of Nanoparticles Containing Ethanolic Extract of Cocculus pendulus in High Fat Fed Rats - Ramala , Sampath Kumar; Alagumanivasagam, G.; Muthu, A. Kottai (Challenges and Advances in Pharmaceutical Research Vol. 2, 2022)
An abnormal presence of lipids in blood leads to cardiovascular disease (CVD). The main objective of the present study was formulation of nanoparticles by using ethanolic extract of Cocculus pendulus and evaluation of hypolipidemic activity in rats fed with high fat diet. Preliminary phytochemical analysis of whole plant of Cocculus pendulus revealed the presence of various phytoconstituents like alkaloids, phytosterols, flavonoids, triterpenes and volatile oils. HPTLC fingerprint analysis of ethanolic extract of plant Cocculus pendulus reveals presence of 13 peaks and 10 peaks in 256 nm and 366 nm respectively and GC-MS shows presence \(β\)-Sitosterol as a marker compound. Nanotechnology is a promising technique to increase the bioavailability of herbal medicines. The formulation of nanoparticles of ethanolic extract of Cocculus pendulus by using Solvent evaporation technique was employed for the preparation of nanoparticles with different polymers concentration and finally the optimized nanoformulation demonstrated a mean particle size, polydispersity index, zeta potential are 536 nm, 0.256, and - 16.4 mV respectively. Antiatherogenic activity was performed on male Wistar rats with 7 groups 6 animals each with doses of ethanolic extract 200, 400 mg/kg and optimized nanoparticles with 40, 80 mg/kg Effect of ethanolic extract of Cocculus pendulus and nano formulations with two different doses on 8 weeks with High fat diet were investigate. Finally results shows that per oral route of administration of Cocculus pendulus and Nano formulations at two doses level showed significant reduction in inclined levels of body weight, total cholesterol, low density lipoprotein, phospholipids, triglycerides, VLDL levels and similarly significant increase in high density lipoproteins levels. Hypolipidemic activity of Cocculus pendulus nanoparticles with dose of 40 mg/kg and 80mg/kg are more effective than the ethanolic extract Cocculus pendulus at a dose of 200 mg/kg, 400 mg/kg.